Deep Ground Truth Analysis of Current Android Malware - Wei, Fengguo; Li, Yuping; Roy, Sankardas; Ou, Xinming; Zhou, Wu (Detection of Intrusions and Malware, and Vulnerability Assessment, 2017)
To build effective malware analysis techniques and to evaluate new detection tools, up-to-date datasets reflecting the current Android malware landscape are essential. For such datasets to be maximally useful, they need to contain reliable and complete information on malware’s behaviors and techniques used in the malicious activities. Such a dataset shall also provide a comprehensive coverage of a large number of types of malware. The Android Malware Genome created circa 2011 has been the only well-labeled and widely studied dataset the research community had easy access to (As of 12/21/2015 the Genome authors have stopped supporting the dataset sharing due to resource limitation). But not only is it outdated and no longer represents the current Android malware landscape, it also does not provide as detailed information on malware’s behaviors as needed for research. Thus it is urgent to create a high-quality dataset for Android malware. While existing information sources such as VirusTotal are useful, to obtain the accurate and detailed information for malware behaviors, deep manual analysis is indispensable. In this work we present our approach to preparing a large Android malware dataset for the research community. We leverage existing anti-virus scan results and automation techniques in categorizing our large dataset (containing 24,650 malware app samples) into 135 varieties (based on malware behavioral semantics) which belong to 71 malware families. For each variety, we select three samples as representatives, for a total of 405 malware samples, to conduct in-depth manual analysis. Based on the manual analysis result we generate detailed descriptions of each malware variety’s behaviors and include them in our dataset. We also report our observations on the current landscape of Android malware as depicted in the dataset. Furthermore, we present detailed documentation of the process used in creating the dataset, including the guidelines for the manual analysis. We make our Android malware dataset available to the research community.